Delays in Infant Hearing Detection and Intervention During the COVID-19 Pandemic: Commentary. (April 2022) - Jenks, Carolyn M.; DeSell, Melinda; Walsh, Jonathan
Early detection and intervention for congenital hearing loss are critical for speech and language development. Newborns should receive hearing screening, diagnosis, and intervention by 1, 3, and 6 months, respectively. The COVID-19 pandemic has caused delays in each step of this process. Increased out-of-hospital births and shortages of essential health care services likely reduced the proportion of newborns completing screening. Additional factors have contributed to delayed diagnosis. We estimate that up to 50% of infants born with hearing loss in Maryland in 2021 may be delayed in diagnosis. Hearing loss interventions have been affected due to delayed initiation, reduced availability, and lack of in-person services. Delayed diagnosis and treatment of congenital hearing loss are likely to have significant effects on individual patients and public health, the full magnitude of which will not be known for years. Opportunities exist for providers to mitigate the negative effects of COVID-19 on pediatric hearing health care.